EFEKTIVITAS PENGGUNAAN MEDIA GAMBAR SERI DALAM PEMBELAJARAN MENULIS TEKS CERPEN - Sakaria Sakaria; Asia M Asia M; Nurul Asmaul Husnah (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the effectiveness of using serial picture media in writing short stories for class IX junior high school students. The type of research used by the researcher in this study is a quasi-experimental design model, pretest-posttest control group design. The population in this study were all students of class IX SMP Negeri 29 Makassar, amounting to 253 and divided into 10 classes. Sampling was done by purposive sampling technique. Based on the results of the sample selection, class IX1 was determined as the experimental class and IX2 as the control class which consisted of 24 students in each class. The results of the study indicate that the serial picture media is effectively used in learning to write short stories. This can be proven from the results of the paired sample test learning outcomes for the experimental class posttest and posttest control class, the value of tcount is 3,448 ttable, which is 3,448.